Modeling of pipeline thermal dynamics in cargo heating system and bubble dynamics with effects of shear flow and temperature gradient - Hong, Jiahua (Nanyang Technological University, 2015)
The transport of crude oil by oil tankers in a long distance requires a huge amount of fuel to heat the oil and maintain it at a certain safe temperature. For oil transportation purpose, steam is usually used to heat up the crude oil. The transport of steam and water in the pipelines is associated with a substantial amount of energy loss to the surrounding environment, which significantly increases the fuel consumption in the boiler. In order to efficiently reduce the fuel consumption, it is crucial to fully understand the fundamental mechanism of heat loss in the pipeline system. The thesis consists of the two portions (1) thermodynamic analysis of the pipeline in cargo heating system, and (2) simulation of bubble dynamics with the effects of shear flow and temperature gradient. • The first portion works on the investigation of the heat transfer performance for both the steam and water pipelines. Since the pipeline system is installed on deck and suffering the weather conditions directly, the heat transfer mechanism is dominated by convection heat transfer. In particular, the condensation process has a great influence on the heat and mass transfer process of the steam pipeline. The heat transfer characteristic of the pipeline system is numerically investigated by the commercial computational fluid dynamics (CFD) software, ANSYS FLUENT (v14.0). The sensitivity studies are conducted first to find the appropriate mesh size and time-step for the steam and water pipelines. The parametric studies are then carried out for investigating the heat transfer performances of the pipeline system. It is found that the wind speed and the ambient temperature have a great impact on the temperature and heat loss of the pipeline system. It is also indicated that the efficiency is low when the mass-flow rate is small. It is observed that the thermal insulation with the thickness of effectively reduces more than heat loss of the pipeline. Since the CFD simulation is time-consuming, a theoretical model is finally developed for fast prediction of the heat loss of the pipeline. By comparison between the theoretical model and the CFD simulation, it is demonstrated that the accuracy of the theoretical model is acceptable for the current research work. • The second portion works on the simulations of bubble dynamics with the effects of shear flow and temperature gradient. The reason for the present second portion work is that the gas bubbles generally exist inside the water pipeline, which may affect the heat transfer characteristics of the pipeline system. An in-house code based on the immersed boundary method (IBM) is adopted for the investigation of the single-bubble dynamics, which solves a set of governing equations for the entire computational field on the Eulerian grid, and tracks the interface of the bubble on the Lagrangian grid. The sensitivity studies are conducted first on the mesh size and time-step. The results of the present IBM code are then compared with the previous published works. Subsequently, the cases studies are carried out for analysis of the effects of shear flow and temperature gradient on bubble dynamics. Firstly, the effects of Reynolds number and boundary confinement are discussed in details subject to shear flow and temperature gradient, separately. Secondly, in terms of the effects of the shear flow coupled with temperature gradient, the simulation results are compared with those with shear flow effect only, and then the influence of the direction between the shear flow and temperature gradient is also investigated on the bubble deformation.